Access: Net Prices, Affordability, and Equity At A Highly Selective College - Catharine B. Hill; Gordon C. Winston (Williams College, Williams Project on the Economics of Higher Education (WPEHE), 2001)
All of the financial aid decisions at Williams College for the past fourteen years - nearly 14,000 of them - were used to see how much students actually paid for tuition, room, board, and fees to go to that highly selective and expensive school - their net prices. Williams practices need blind admission with full need-based financial aid and gives neither merit nor athletic scholarships - a family?s economic circumstances are the only reason for a price adjustment. So these data can answer the motivating question of the study, ?Can highly able low income students reasonably aspire to go to the best and most expensive colleges in the country?? Does need-blind admission and full need financial aid, in other words, really work to serve merit and equity at the same time? With income and net price data on all aided students and income data for families at the 95th and 99th percentiles of the US income distribution who pay the full sticker price, we can describe the net price pattern across the whole student population as pricing policies have evolved at Williams (and similarly at other highly selective schools). The end point - in the current academic year - sees a remarkable similarity in the shares of income paid for a year at Williams. Aided students across the five income quintiles pay, on average, 11% to 19% of their pretax family incomes - the lowest income quintile paying the smallest share - while those at the 95th and 99th percentiles, paying full price, spend 21% and 9% of their family incomes, respectively, for a year at Williams. One usefully concrete number: the average student in the bottom twenty percent of the income distribution pays 1,683 while the full tuition is 32,470.
Keywords: 330; Studienfinanzierung; Bildungschancen; Studium; USA; Hochschulzulassung